Kesenjangan Digital Dalam Pemanfaatan Tiket Elektronik Pada Angkutan Massal Trans Padang - Mutiara Laudya; Ria Ariany; Muhammad Ichsan Kabullah (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2023)
This research aims to describe the form of  digital divide that occurs in the utilization of electronic tickets of mass transportation Trans Padang. This research used the main traditional theory of digital divide according to Spark Collin 2013, which is to identify the digital divide than can be seen from the access, skills & cultural competence, and internet use & social reproduction. Using a qualitative approach with a descriptive type. Data collection techniques used are interviews, observation, and documentation. Furthermore, for data validation of the data, researchers used source triangulation. The results of this study indicate that there is a digital divide that still existed in the utilization of electronic tickets of mass transportation Trans Padang, The digital divide can be seen in the material indicators of access and usage patterns. Still, experience obstacles such as the lack of affordability of the purchasing price Brizzi cards are unaffordable for some passengers and limited literacy about  digital finance from passengers who only use Brizzi for Trans Padang.Besides material and usage patterns, age  and education factors also affect the ability of passengers to use electronic tickets.Divide still existed for older passengers and passengers with low education who are less familiar with technology so they still experience difficulties in paying Trans Padang payments. However, when seen as a whole, the overall level of digital divide in the use of Trans Padang electronic tickets Has decreased compared to the beginning of cashless payments implementation. This is also showing a change in the habit of using digital technology that is caused by the Covid-19 pandemic.